Transformation groups : symplectic torus actions and toric manifolds - Mukherjee, Goutam; Allday, C.; Masuda, Mikiya; Sankaran, Parameswaran (New Delhi : Hindustan Book Agency, 2005)
Contributed lectures presented earlier at Winter School on Transformation Groups.
Keywords: Transformation groups; Torus (Geometry); Manifolds (Mathematics)